Análise de metodologias de ensino de Química para debater a temática biodiesel à luz do enfoque CTSA : alfabetização científica no ensino médio - Silva, Marcio Corrêa da (2012)
This work had as one of its objectives to evaluate how the Biodiesel inserted in the teaching of Chemistry could be used as a generator theme within the study of the environmental area for fifteen students enrolled in a federal institution high school and for forty students enrolled, also in high school at a private school, from February to July 2011, both located in Vitória, Espírito Santo. It can be seen through a theoretical basis and through the reflection of current Chemistry teaching in the classroom, on generator themes arguing about an active and transformative environmental education. The use of Chemistry is seen by many authors as the cause of environmental impacts such as pollution, poisons, insecticides, preservatives, additives and pesticides. However, you can also use these teachings to awaken the spirit of awareness on the students of their role as educated citizens active in the search for environment preservation. Based on several authors as Loureiro (2005) and Guimarães (2004), Guimarães and Vasconcellos (2006), Saito (2002) and Leff (2001), we have attempted to discuss the generator themes, postulated by Freire (2005, 2007), to contextualize the importance of studying the environment. A qualitative study was undertaken from the perspective of an active search. The data evaluation consisted of the analysis of the answers given by students from the questionnaires answered by them before and after the methodological approaches appropriate to the theme of Biodiesel. The questionnaires contained questions consisting of various items related to the students knowledge of Biodiesel in addition to questions that allowed the evaluation of these students regarding their understanding with respect to the easiness and difficulties found by them in relation to Chemistry. We conclude that through the analysis of the data, which is not only possible, but necessary that the school create mechanisms so that their teachers come to develop activities related to the generator themes